2020
DOI: 10.1177/0165551520962781
|View full text |Cite
|
Sign up to set email alerts
|

Deep Persian sentiment analysis: Cross-lingual training for low-resource languages

Abstract: With the advent of deep neural models in natural language processing tasks, having a large amount of training data plays an essential role in achieving accurate models. Creating valid training data, however, is a challenging issue in many low-resource languages. This problem results in a significant difference between the accuracy of available natural language processing tools for low-resource languages compared with rich languages. To address this problem in the sentiment analysis task in the Persian language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Also, they attempted to address challenges in Persian language by applying DL methods which only achieved the f-score of 55.5%. Ghasemi et al [112] developed a sentiment analysis task in Persian language by proposing a cross-lingual deep learning framework to benefit from available training data of the English language. Deep learning models such as CNN and LSTM and their combinations were experimented with to achieve the fscore of 91.8% on LSTM-CNN.…”
Section: Emerging Msa Areasmentioning
confidence: 99%
“…Also, they attempted to address challenges in Persian language by applying DL methods which only achieved the f-score of 55.5%. Ghasemi et al [112] developed a sentiment analysis task in Persian language by proposing a cross-lingual deep learning framework to benefit from available training data of the English language. Deep learning models such as CNN and LSTM and their combinations were experimented with to achieve the fscore of 91.8% on LSTM-CNN.…”
Section: Emerging Msa Areasmentioning
confidence: 99%
“…At first, two novel deep learning architectures, including bidirectional LSTM and CNN, are proposed, which are designed and can classify sentences in both cases. Then, three data augmentation methods are proposed for the low-resources Persian sentiment corpus [11]. In [22], the authors proposed a transfer learning algorithm based on cellular learning automata (CLA) to reduce negative transfers.…”
Section: Binary Sentiment Classificationmentioning
confidence: 99%
“…The most recent research has been on English and languages that have sufficient resources. Still, limited research has been done in low-source languages such as Persian to identify emotional states, and most of this research has identified positive and negative polarity [11]. In recent years, deep learning has been used to solve many problems related to natural language processing and sentiment analysis of texts, which has performed better than previous methods [44].…”
Section: Related Workmentioning
confidence: 99%
“…e online social network sentiment analysis and detection model based on user characteristics can improve the accuracy of detection to a certain extent, but at the same time, there are serious problems because normal users will spread the social network sentiment analysis without knowing it, so the misjudgment rate of this method is relatively high. Cue words in the text are constructed and analyzed in an attempt to predict early social network sentiment analysis [17]. For the health-related social network sentiment analysis, the characteristics of information sources of samples were analyzed, such as the URL and site name of the information source website, and then the logistic regression model was used to test the online social network sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%